2020
DOI: 10.1016/j.clnu.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Acute stroke patients not meeting their nutrition requirements: Investigating nutrition within the enriched environment

Abstract: Background/Aims: Malnutrition is common after stroke. We investigated the impact of environmental enrichment strategies on dietary intake and rates of malnutrition in an acute stroke unit. Methods: We performed a before-after study. In standard care, meals were delivered to participants' rooms whilst in the enriched environment, communal meals with assistance were offered and nutritional intake reminders were placed at the patient bedside. Nutrition supplementation was provided to both groups if indicated. Bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Even still, the primary objective of this review was not to compare effects but to compile research on EE. Therefore, the studies included in this review showed modest effects ( Janssen et al, 2022 ) or no improvement ( Robertson et al, 2020 ). Second, comparing studies that use different methods, such as quantitative and qualitative, may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Even still, the primary objective of this review was not to compare effects but to compile research on EE. Therefore, the studies included in this review showed modest effects ( Janssen et al, 2022 ) or no improvement ( Robertson et al, 2020 ). Second, comparing studies that use different methods, such as quantitative and qualitative, may be challenging.…”
Section: Discussionmentioning
confidence: 99%
“…This may have contributed to the relatively high prevalence risk of malnutrition. Several studies have described the energy and protein intake of stroke patients during acute admission or in the rehabilitation ward ( 14 , 40 45 ). However, to the best of our knowledge, the present work is probably one of the few that compared nutrient intakes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Подходы к ведению пациентов с острыми нарушениями мозгового кровообращения (ОНМК) предусматривают широкий комплекс терапевтических и хирургических направлений лечения. Одним из важнейших элементов интенсивной терапии инсульта является нутритивная поддержка [1,2].…”
Section: Introductionunclassified